2016
DOI: 10.1016/j.bbi.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Spinal inhibition of p38 MAP kinase reduces inflammatory and neuropathic pain in male but not female mice: Sex-dependent microglial signaling in the spinal cord

Abstract: Previous studies have shown that activation of p38 mitogen-activating kinase (MAPK) in spinal microglia participates in the generation of inflammatory and neuropathic pain in various rodent models. However, these studies focused on male mice to avoid confounding effects of the estrous cycle of females. Recent studies have shown that some spinal pro-inflammatory signaling such as Toll-like receptor 4-mediated signaling contributes to pain hypersensitivity only in male mice. In this study we investigated the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
232
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(254 citation statements)
references
References 78 publications
(126 reference statements)
19
232
0
3
Order By: Relevance
“…Three distinct MAPK pathways have been described in mammalian cells, including the ERK pathway, the JNK pathway, and the p38 MAPK pathway (25). The present study demonstrated that transfection of SW48 cells with the TGFBR1*6A plasmid resulted in the upregulation of p-p38 and p-ERK protein expression.…”
Section: Discussionsupporting
confidence: 52%
“…Three distinct MAPK pathways have been described in mammalian cells, including the ERK pathway, the JNK pathway, and the p38 MAPK pathway (25). The present study demonstrated that transfection of SW48 cells with the TGFBR1*6A plasmid resulted in the upregulation of p-p38 and p-ERK protein expression.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, strong or weak expression of p-p38 predicts whether nerve cells are alive (27). As a result of the apoptosis process of neurons and colloid cells subsequent to SCI, p-p38 expression increases, indicating that the p-p38 signal transduction pathway is altered after SCI (28). SCI results in the activation of p-p38, which then increases NOS activity and promotes apoptosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia have also been shown to be involved with orofacial pain (Fan et al 2010;Ma et al 2015); activation of the P2X7 receptor in microglia of trigeminal nucleus facilitates extraterritorial facial pain via TNF-α secretion following transection of the mental nerve, the third branch of the trigeminal nerve (Murasaki et al 2013). Recent studies have found that the role of microglia in pain also depends on sex (Sorge et al 2015;Taves et al 2015).…”
Section: Introductionmentioning
confidence: 99%